(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
:“Mass Media with its sixty plus years history and its perceived capability to directly affect large audience has enormous capacity to communicate for and about development. Especially, Television has been continuously evolving as the most ‘massive’ of the media in terms of reach, time spent and popularity, has barely changed over thirty years and it add all the time to its global audience” (Mc Quail, 2010: 35) Wilkins (2008) opines that participation ,of the stakeholders, particularly the marginalized communities , in the developmental process is mandatory in a democratic system. Conceptualizations and justifications for participatory development come under a comprehensive spectrum spanning from recognition of the process to the consequences resulted upon the society. Development practitioners, professionals and governments all over the world have been exploring ways to maximize participation of beneficiary communities in the process as one of the key factors contributing to success. Participation is a tool that helps development planners to utilize indigenous skills of the communities in the process and integrate new knowledge into the communities as well. Some development institutions consider participation is a one-off thing that occurs in the mid of the total process. participation and mobilization can be promoted as a part of media coverage. Wilkins (2008) discusses about the way media communicates on development, questioning the way that social change projects articulate assumptions about problems, solutions, and communities while emphasizing that the ongoing discussion on communicating about development contribute towards improving strategies for communication for development. Hence this research study will examine how the documentary genre in television media frame issues pertaining to poverty and how producers in Sri Lankan television industry identify their role within the context of poverty; what factors influence the television to discuss poverty among rural poor. The findings may conclude whether television has been utilized fully for the benefit of rural community and to what extent the rural poverty is discussed in that media, with suggestions to improve the television output to reduce the knowledge gaps among rural poor, improve participation and reduce rural poverty.